PENGARUH MODEL PAIR CHECKS TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 10 PANGKALANBARU - Elis Anggrayani; Diana Pramesti; Feri Ardiansah (JURNAL PENDIDIKAN DASAR, 2021)
The research was carried out at SDN 10 Pangkalanbaru. It was found that in Social Studies learning the learning outcomes obtained were low, almost 60% of students scored under the Minimum Completeness Criteria, Lack of teacher creativity in varying the learning model inotherclassroom. The research method used is Quasyoexperiment andothe0research model is NonequivalentoControloGroupuDesign. The sampling technique uses saturated sampling. Test the validity using the Product Moment person correlation. The reliability coefficient of rcount is 0.830 and rtable is 0.304. Normality test uses the Kolmogorov Smirnov test. The results of calculations in the Pair checks learning model class obtained Lcount Ltable 0.133 0.250 and the control class Lcount Ltable 0.133 0.250 the data was declared to be normally distributed. Homogeneity test using Fisher's exact test. The results of the calculation of Fcount Ftable (1.161 1.880) then the variance of the two groups is homogeneous. Hypothesis testing Independent sample t-test obtained tcount 3,989 and ttable 2,006 tcount ttable then H0 is rejected and H1 is accepted. The results of this study concluded that there was an effect of the use of the Pair checks learning model on the fourth grade of SDN 10 Pangkalanbaru.Keywords: Pair checks Learning Model, Social Studies Learning Outcomes